2020
DOI: 10.3390/app10061953
|View full text |Cite
|
Sign up to set email alerts
|

Urban PM2.5 Concentration Prediction via Attention-Based CNN–LSTM

Abstract: Urban particulate matter forecasting is regarded as an essential issue for early warning and control management of air pollution, especially fine particulate matter (PM2.5). However, existing methods for PM2.5 concentration prediction neglect the effects of featured states at different times in the past on future PM2.5 concentration, and most fail to effectively simulate the temporal and spatial dependencies of PM2.5 concentration at the same time. With this consideration, we propose a deep learning-based meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 26 publications
0
31
0
2
Order By: Relevance
“…The first one (i.e., AE-BiLSTM) is a combination of auto-encoder and bi-LSTM neural network [21]. The second one, AC-LSTM proposed in [22], lever-…”
Section: A Evaluation Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one (i.e., AE-BiLSTM) is a combination of auto-encoder and bi-LSTM neural network [21]. The second one, AC-LSTM proposed in [22], lever-…”
Section: A Evaluation Settingsmentioning
confidence: 99%
“…This section compares our ED-LSTM to AE-BiLSTM [21], AC-LSTM [22], and ST-DNN [11]. Since all three models' source codes are not publicly available, we have initially reimplemented them.…”
Section: Comparing Prediction Modelsmentioning
confidence: 99%
“…e attention mechanism was originally used in machine translation [34], but it is now an important part of neural network structures, and it is also widely used in image processing, speech recognition, and computer-related fields [35]. In the recent literature, Li et al [36] proposed to use the attention mechanism to capture the most important part of the past state, but ignored the relative importance of neighboring sites. In addition, non-time series (road network and POI) also affects the prediction of the target area.…”
Section: Related Workmentioning
confidence: 99%
“…6 have applied three machine learning models that forecasted PM2.5 concentrations and their results showed that the variability was 80% (R 2 = 0.8) in the concentrations of PM2.5 and 75% of the pollution levels were predicted. 7 made an attention mechanism to capture the degree of signi cance of the effects on future concentrations of PM2.5 of the featured states at different times in the past. 8 have studied the PM2.5 using Interagency Monitoring of Protected Visual Environments (IMPROVE) and Chemical Speciation Network (CSN).…”
Section: Introductionmentioning
confidence: 99%